When Does Vegetation Establish on Gravel Bars? Observations and Modeling in the Alpine Rhine River - Caponi, Francesco; Koch, Aurélie; Bertoldi, Walter; Vetsch, David F.; Siviglia, Annunziato (Frontiers in Environmental Science, 2019)
Predicting when riparian vegetation establishes on river bars is crucial to estimate how morphology and ecology of gravel bed rivers respond to anthropogenic or climatic changes. However, the characteristic timescale required for vegetation establishment on gravel bars remains poorly investigated. The Windows of Opportunity (WoO) concept provides an ideal framework for estimating such timescale by analysing time series of disturbance periods following seed dispersal. Here we present the results of a study conducted in a 41 km long reach of the Alpine Rhine river characterised by the presence of alternate gravel bars, which show differences in morphological activity and vegetated areas. We mapped the time evolution of vegetation cover between 1996 and 2017 by using aerial images and related vegetation occurrence to bar topography. Observations show that vegetation mainly colonised bar surfaces between 2005 and 2008, enduring on bars that showed less morphological activity. Only few patches, which were removed by downstream bar migration, were observed on bars that experienced significant morphological changes. This allowed us to identify conditions that were more favourable to vegetation recruitment and growth. To explain the vegetation pattern observed along the whole reach, we developed a simple modelling framework based on the WoO concept including the effects of flow variability on seed dispersal and seedling recruitment and survival. Model applications demonstrate that vegetation successfully establishes on bare areas if plants can withstand hydrodynamic disturbances for about 85 days after seed dispersal. We also identified timing and location of successful recruitment events and discussed how they are linked to bar morphology, seed dispersal, and riverbed morphodynamics. This study provides a first attempt to quantify the WoO in a gravel bed river with alternate bars, representing a step towards the development of quantitative tools for predicting river morphological trajectories.